Teachers' efforts to improve discipline of elementary school students using positive reinforcement methods in online learning - Tantu, Year Rezeki Patricia; Eleison Oloi Marina, Kirey (Universitas Nusantara PGRI Kediri, 2023)
: Discipline is an attitude that students need to have in learning in order to help students achieve learning goals. On the other hand, learning aims to train discipline so that students can behave correctly and have good character in society. This study aims to examine teachers' efforts to use positive reinforcement in increasing student discipline in the learning process. The research method used is descriptive qualitative. The data found by the author shows that the percentage of discipline in grade IV elementary school students is 63.2%. The teacher applies a positive reinforcement method that aims to improve student discipline. The use of positive reinforcement methods shows an increase in student discipline to 73.3%. The teacher has a role as a role model and guide in building student character. The conclusion obtained is that positive reinforcement shows the percentage of success of positive reinforcement on student discipline of 10.1%. The advice given is to make more specific disciplinary indicators and research is carried out over a longer period of time so that discipline improvements are more visible.